THE FORMATION OF A SYSTEM OF RELATIONSHIP BETWEEN EDUCATIONAL INSTITUTIONS AND EMPLOYERS - Oleg V. Motovilov (Высшее образование в России)
The article clarifies the content of «employer» concept. It is noted that in addition to the institutional approach, which focuses mainly on the different types of organizations that can act as employers, it is important to take into account the personal approach. It is connected with the fact that experts, acting as the employer's representative, often actually represent only themselves. The paper discusses the basic options for employer participation in the educational process, including relatively new: participation in the work of the specialized Councils on education programs, reviewing final qualifying works, participation in the state examination commissions, etc. The author's reasoning is based on the past experience, in particular, he emphasizes the undesirability to staff state examination commission only with the representatives of employers.